2018
DOI: 10.1007/s40119-018-0109-y
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Embolism Following Incomplete Surgical Resection of a Right Ventricular Myxoma: A Case Report and Review of the Literature

Abstract: Right ventricular (RV) myxomas are extremely rare, but may have dreadful clinical sequelae including pulmonary embolism (PE). We present a case of a patient who had an RV myxoma that was attached to the tricuspid valve, and therefore could not be resected completely during surgery, and remnants of the tumor were seen on transthoracic echocardiogram during post-operative follow-up. Five months after surgery, the patient had PE, which could be due to tumor emboli or thromboemboli. Since repeat surgical resection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…A recurrence of right ventricle myxoma with pulmonary embolization was reported also in a 28-years-old patient because of an incomplete resection due to the adherence of the tumor to the tricuspid valve [33].…”
Section: Narrative Review Of Literature and Discussionmentioning
confidence: 83%
“…A recurrence of right ventricle myxoma with pulmonary embolization was reported also in a 28-years-old patient because of an incomplete resection due to the adherence of the tumor to the tricuspid valve [33].…”
Section: Narrative Review Of Literature and Discussionmentioning
confidence: 83%
“…However, there is no clear guideline for treating pulmonary embolisms combined with right ventricular tumors. One study reported the use of warfarin to treat a pulmonary embolism following incomplete surgical resection of a right ventricular myxoma, with no recurrence of emboli after 20 months [ 5 ]. Another case study reported resection of a right ventricular myxoma of 9.5 × 5.0 cm.…”
Section: Discussionmentioning
confidence: 99%
“…Yazan Assaf et al . reviewed 12 patients with pulmonary infarcts caused by cardiac tumors and pulmonary tumor emboli . Approximately 10% of patients with metastatic cardiac tumors develop cardiac dysfunction.…”
Section: Discussionmentioning
confidence: 99%